Secondary hemophagocytic lymphohistiocytosis in children with dengue: A case series - Nirosha Ponnuraj; Manoj Kumar; Saravanan Muthuarumugam; Reghupathy Panneerselvam (Wolters Kluwer Medknow Publications, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is a rare, potentially lethal condition characterized by the activation of macrophages, natural killer cells, and T-cells, leading to a dysregulated immune response. Genetic mutations cause primary HLH; infections, tumors, or autoimmunity can trigger secondary HLH. Dengue infections can rarely be complicated by secondary HLH, which is a potential cause of mortality apart from shock or hemorrhage. A high index of suspicion is needed as clinical features are nonspecific and overlap with dengue. We report three children with dengue infection complicated by secondary HLH. All three children recovered with timely management.